Prevention of Sudden Cardiac Death in Adults With Congenital Heart Disease: Do the Guidelines Fall Short?. (July 2017) - Vehmeijer, Jim T.; Koyak, Zeliha; Budts, Werner; Harris, Louise; Silversides, Candice K.; Oechslin, Erwin N.; Bouma, Berto J.; Zwinderman, Aeilko H.; Mulder, Barbara J.M.; de Groot, Joris R.
Abstract : Background—: Sudden cardiac death (SCD) is a major cause of mortality in adult congenital heart disease (ACHD) patients. SCD may be prevented by implantable cardioverter-defibrillator (ICD) implantation, but patient stratification remains troublesome. The 2014 Consensus Statement on Arrhythmias in ACHD patients and the 2015 European Society of Cardiology Guidelines specified recommendations for ICD implantation in ACHD patients for the first time. We assess the discriminative ability of these ICD recommendations for SCD in ACHD patients. Methods and Results—: Of 25 790 ACHD patients in an international multicenter registry, we identified all SCD cases, matched to living controls by age, sex, congenital defect, and surgical repair. We assessed all primary prevention ICD recommendations listed in both documents. We used conditional logistic regression models to calculate odds ratios and receiver operating characteristic curves with area under the curve. Consensus Statement: One hundred twenty-four cases (median age at death, 33 years [26–44]; 67% men) and 230 controls were studied. In total, 41% of SCD cases and 17% of controls had an ICD recommendation (odds ratio, 5.9; P <0.001). European Society of Cardiology Guidelines: Of one hundred fifty-seven cases (median age at death, 33 years [26–48]; 64% men) and 292 controls, 35% and 14% had an ICD recommendation, respectively (odds ratio, 4.8; P <0.001). Conclusions—: A minority of SCD cases had an ICD recommendation according to these guidelines, whereas the majority of SCD victims remained unrecognized. With an area under the curve of 0.6 to 0.7, the discriminative ability of both guidelines was mediocre. Critical clinical reasoning when deciding on ICD implantation in ACHD patients, therefore, remains vital.